Dosimetric Parameter Analysis of Stereotactic Radiosurgery on Vestibular Schwannoma with Intensity-Modulated Radiotherapy Step-and-Shoot, Volumetric-Modulated Arc Therapy and Helical Tomotherapy - Soehartati A. Gondhowiardjo; Aurika Sinambela; Handoko Handoko; Arie Munandar; Wahyu Edy Wibowo; Sri Mutya Sekarutami; Angela Giselvania (Radioterapi & Onkologi Indonesia, 2021)
Introduction: SRS is a non-invasive modality in management of vestibular schwannoma. There is limited study comparing dosimetric parameters between three techniques SRS in vestibular schwannoma cases, thus IMRT Step and Shoot (IMRT-SS), VMAT, and Helical Tomotherapy (HT). Aim: To compare the dosimetry parameters on SRS among IMRT-SS, VMAT, and HT techniques on Vestibular ScwhanomaMethod: Treatment planning with IMRT-SS, VMAT, and HT on eleven CT plan data for schwannoma vestibular cases. The marginal dose is 12 Gy with single fraction. Results: Mean tumor size was 8.23 cm + 5.08 cm3. No significant difference were found in the mean CI, GI, V100%, and V50% among three techniques. There was no significant difference in maximal dose to brainstem, ipsilateral cochlea, chiasma opticum, ipsilateral and contralateral optic nerve between the three techniques. There was significant difference of maximum dose on contralateral cochlea between IMRT-SS and VMAT techniques. The longest beam-on time was obtained with HT technique (1209,18 +390,20 second), followed by IMRT-SS technique (665,05 + 73,40 second), and the shortest was with VMAT technique (362,87 + 24,55 second). There was significant difference in mean MU and beam on time between three techniques. Conclusion: VMAT technique could be an option for SRS for vestibular schwannoma cases to provide conformity and gradient index as well as IMRT-SS and HT techniques, with better sparing to contralateral cochlea compared with IMRT-SS technique, and provides shorter beam-on time rather than IMRT-SS and HT.